Dilute suppressor dsu acts semidominantly to suppress the coat color phenotype of a deletion mutation, dl20J, of the murine dilute locus. - Moore, K J (1988)
The murine dilute suppressor (dsu) gene is the only unlinked trans-acting suppressor identified in mammals. dsu, which was originally reported to be recessive, was recognized by its ability to suppress the coat color phenotype of a retroviral insertion mutation, dv, of the murine dilute (d) locus. This insertion mutation resulted from the integration of an ecotropic murine leukemia virus into noncoding sequences of the dilute gene. Therefore, dsu may act like other allele-specific recessive suppressors identified in Drosophila melanogaster and yeast that suppress mutations induced by retrotransposon insertions. To investigate this possibility, we have examined whether dsu could suppress a spontaneously arising allele of d, dl20J, which is shown here to result from a 3.5-kilobase deletion. These studies indicate that dsu does not function like other eukaryotic suppressor genes that suppress retrotransposon-induced mutations. We also show that dsu is not, as originally reported, a recessive gene but is semidominantly inherited. Collectively, these results allow us to propose a mechanism for the suppressor activity of dsu.